Can budget participation and budgetary slack increasing managerial performance? - Prabawanto, Ahmad; Rustiana , Siti Hamidah; Sulhendri, Sulhendri (Tekmapro, 2024)
This research aims to determine the effect of budgetary slack on managerial performance. The method used is quantitative with a type of causality research. The sample determination method uses purposive sampling. The analysis technique used in this research is PLS (Partial Least Squares). The total sample in this study was 134 respondents who were employees of PT Bukit Makmur Mandiri Utama. The results of this research are that budgetary slack has a significant negative influence on managerial performance, budget participation has a significant positive influence on managerial performance.